2016
DOI: 10.1111/jdv.13865
|View full text |Cite
|
Sign up to set email alerts
|

Optimal maintenance treatment with calcipotriol/betamethasone dipropionate gel in Korean patients with psoriasis vulgaris: a multicentre randomized, controlled clinical trial

Abstract: Among Korean patients with psoriasis vulgaris, maintenance treatment with calcipotriol monohydrate/betamethasone dipropionate using a continuous daily regimen or an 'as needed' daily regimen provided similar efficacy, whereas a twice-weekly regimen was significantly less efficacious than either of these regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…Additionally, 22 papers were obtained from LEO Pharma (Figure 1). Twenty‐five publications were included in the systematic review 13‐37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 22 papers were obtained from LEO Pharma (Figure 1). Twenty‐five publications were included in the systematic review 13‐37 …”
Section: Resultsmentioning
confidence: 99%
“…Of those that did, two RCTs found that more versus less frequent application of Cal/BD was more efficacious. In a study of Korean patients, treatment with Cal/BD using a continuous daily regimen or an ‘as needed’ daily regimen were similarly efficacious, whereas a twice‐weekly regimen was significantly less efficacious than either of these regimens 25 . A twice‐weekly regimen was more efficacious than a once‐weekly regimen of Cal/BD in a study of Chinese patients, with no difference noted between the twice‐weekly regimen and a group randomized to once‐daily Cal 36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The twice‐weekly Cal/BD maintenance regimen provided comparable efficacy as daily treatment with calcipotriol, and both regimens were significantly more effective than once weekly Cal/BD ointment. Patients with limb or trunk PsO who achieved disease control after 8 weeks of daily treatment with Cal/BD gel were randomized to either maintain once daily treatment continuously or as needed, or to twice weekly treatment on weekends for a further 8 weeks in a small Korean study 35 . Long‐term daily treatment used either continuously or as‐needed was significantly more effective at maintaining remission than weekend‐only therapy.…”
Section: What Different Topical Maintenance Therapy Regimens Exist?mentioning
confidence: 99%
“…The authors suggest that maintenance therapy should begin when a clinical response is reached, likely after approximately 4 weeks of acute topical treatment. A 4‐week acute treatment period has been used successfully in a scalp PsO maintenance study 32 and in the PSO‐LONG proactive maintenance study of Cal/BD foam, 7 while other studies have used induction phases as short as 2 weeks 37,38 or as long at 8 weeks 35 . Overall, 4 weeks of acute treatment is likely realistic for most patients, but decisions should be individualized since some patients may benefit from earlier or later transition from acute to maintenance therapy.…”
Section: Unanswered Questionsmentioning
confidence: 99%